The concept of image of a higher educational institution as employer (Journal of Economic Research & Business Administration, 2016)
In article the approach to construction of mutual relations of a higher educational institution with the faculty on the basis of the concept of image of a higher educational institution as employer is stated, theoretical bases of this concept are considered, the conceptual device and a scope is defined. Also the technology of studying of image of a higher educational institution as employer.
Keywords: competitiveness of the university; the organization’s im age as an employer; internal and external image of the university as an employer; personnel management; marketing personnel.